EXPLORING THE TYPES AND CHALLENGES OF HEDGES AND BOOSTERS IN EFL STUDENTS’ ACADEMIC WRITING - Merlinda, Riza; Hartono, Hartono; Masduki, Masduki (University of Kuningan, 2025)
This study aims to explore the types based on Bal-Gezegin & Baş (2020) theory and the problems of hedges and booster devices used in the EFL students’ theses. This research applied a qualitative approach, specifically a case study, and the data analysis employed by Miles et al., (2014). The researcher used purposive sampling to determine the research. The participants were six theses and six EFL students at English Education Department of UNU Lampung who studied in 2018 and graduated in 2022. Furthermore, the researcher used a document checklist and interview to gather the data. The research found four types of hedges: modal auxiliaries, lexical verbs, hedging adverbs, and hedging phrases. There were six types of boosters, namely lexical verbs, boosting adverbs, modal auxiliaries, boosting adjectives, boosting nouns, and boosting phrases. Moreover, the problems faced by the students are the learner’s limited knowledge, improper grammar, lack of confidence, difficulty constructing phrases, insufficient experience, overuse, inadequate vocabulary, and misplaced vocabulary. the results pointed out that using hedges and boosters is crucial to help the students understand how hedges and boosters can be used for expressing claims or arguments in academic writing. In sum, this research improved the learners’ understanding of the nuances of academic communication. It highlighted the significance of students and researchers acquiring comprehensive of hedges and boosters.